2023
DOI: 10.1371/journal.pone.0284975
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO and RhD blood groups with the risk of HIV infection

Abstract: Naturally occurring antibodies against ABO antigens present in human sera have been shown to neutralize ABO-expressing HIV in vitro. We investigated associations between ABO and RhD blood groups and HIV infection among blood donors from all blood collection centers in eight of South Africa’s nine provinces. Whole blood donations collected from first time donors between January 2012 and September 2016 were tested for HIV RNA by nucleic acid testing and HIV antibody using third generation serology assays. ABO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…The prevalence of HIV was highest in Afollowed by AB -. This observation opposed the study by Jacobs et al [1,19] which demonstrated higher prevalence in Rhesus positive individual [20]. 8) 13 ( 13) 15 ( 24) 33 ( 11) 27 ( 6) 18 ( 12) 43 ( 14) 38 ( 16) 14 ( 5) 35-45 1 (1) 10 ( 6) 1 ( 1) 5 ( 8) Finally, this study contributes to our understanding of the sero-prevalence of HIV among students undergoing medical examination in a tertiary institution.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The prevalence of HIV was highest in Afollowed by AB -. This observation opposed the study by Jacobs et al [1,19] which demonstrated higher prevalence in Rhesus positive individual [20]. 8) 13 ( 13) 15 ( 24) 33 ( 11) 27 ( 6) 18 ( 12) 43 ( 14) 38 ( 16) 14 ( 5) 35-45 1 (1) 10 ( 6) 1 ( 1) 5 ( 8) Finally, this study contributes to our understanding of the sero-prevalence of HIV among students undergoing medical examination in a tertiary institution.…”
Section: Discussioncontrasting
confidence: 82%
“…The human immunodeficiency virus (HIV) is a chronic viral infectious disease that damages the immune system of the infected individual. It progresses to the development of Acquired Immune Deficiency Syndrome (AIDS) and death without proper medical attention [1]. It is an enveloped lentivirus within the family Retroviridae.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that the ABO blood group was not related to HIV infection. However, the point estimate for OR assesses blood group AB and HIV infection is 1.03 [ 83 ]. Cross-sectional studies cannot be used to infer causality and potential biases should be considered in the observational studies.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Meanwhile, a study from South Africa reported a weak association between Rh-D positive and HIV, and no association of ABO blood type association with TTIs. 30 In a study carried out by Arif et al, 31 AB/Rh-positive blood group was associated with syphilis infection. Still others demonstrated no significant association between ABO and TTIs.…”
Section: Discussionmentioning
confidence: 96%